Accelerated fixed-point formulation of topology optimization: Application to compliance minimization problems. (January 2020) - Li, Weichen; Suryanarayana, Phanish; Paulino, Glaucio H.
Highlights: Accelerated fixed-point formulation of Topology Optimization. Fixed-point iteration accelerated using periodic Anderson extrapolations. Several fold speedup for compliance minimization problems. Abstract: We present a simple, effective, and scalable approach for significantly accelerating the convergence in Topology Optimization simulations. Specifically, treating the design process as a fixed-point iteration, we propose employing a recently developed acceleration technique in which Anderson extrapolation is applied periodically, with simple weighted relaxation used for the remaining steps. Through selected examples in compliance minimization, we show that the proposed approach is able to accelerate the overall simulation several fold, while maintaining the quality of the solution.